Choosing Primary Dental Care Facility: Preference of Indonesian National Health Insurance Participants - M Ikhsan; Syarif Rahman Hasibuan; Nisrina Widyasanti; Ede Surya Darmawan (Jurnal Ilmu Kesehatan Masyarakat, 2025)
The expansion of Indonesia’s National Health Insurance program (Jaminan Kesehatan Nasional, JKN) has improved access to primary dental care services. However, factors influencing participants’ selection of dental care facilities, whether community health centers (pusat kesehatan masyarakat or puskesmas), private clinics, or private dental practices, remain underexplored. This study aimed to identify the determinants of facility preference among JKN participants seeking primary oral health services. The study employed a retrospective cross-sectional design, utilizing secondary data from the 1% Sample Data of Indonesia National Health Insurance (2017–2023). The population consisted of 140,395 adult JKN participants (aged 18 years or older) who received dental care and were alive as of December 31, 2023. Multinomial logistic regression was used to examine the associations between facility choice and sociodemographic variables, including age, sex, premium class, membership segmentation, and residential area. Community health centers were the most accessed (41.1%), followed by private clinics (37.2%). Participants in the government-subsidized segmentation were far more likely to use community health centers (RRR = 16.38; 95% CI: 15.54–17.27). Those in the highest premium class favored private clinics (RRR = 1.29; 95% CI: 1.23–1.35). Residents of Regency had lower odds of visiting community health centers than city residents (RRR = 0.46; 95% CI: 0.44–0.47). These findings indicate that administrative and demographic characteristics have a significant impact on dental care utilization under JKN. Healthcare providers, particularly private clinics and dental practices, should develop value-based strategies centered on service quality and long-term patient relationships. Policymakers may consider capitation adjustments to support quality improvements.